Amphibian loss alters periphyton structure and invertebrate growth in montane streams. Issue 11 (4th October 2022) - Alonso, Alberto; Monroy, Silvia; Bosch, Jaime; Pérez, Javier; Boyero, Luz
Abstract: Amphibians are declining worldwide due to a combination of stressors such as climate change, invasive species, habitat loss, pollution and emergent diseases. Although their losses are likely to have important ecological consequences on the structure and functioning of freshwater ecosystems, this issue has been scarcely explored. We conducted an experiment in three montane streams—where primary production is the main source of energy and carbon—to assess the effects of amphibian disappearance (i.e. presence or absence of the common midwife toad Alytes obstetricans, a common species found in pools of these streams) on several aspects of ecosystem functioning and structure: periphyton biomass and chlorophyll a concentration, algal assemblage structure, and growth of macroinvertebrate grazers. We compared four types of experimental enclosures: (i) without macroinvertebrates or amphibians; (ii) with larvae of the caddisfly Allogamus laureatus ; (iii) with A. obstetricans tadpoles; and (iv) with both A. laureatus larvae and A. obstetricans tadpoles. The absence of tadpoles increased periphyton biomass, but did not cause differences on inorganic sediment accrual. The algal assemblage had a higher diversity in the absence of tadpoles, and their characteristic taxa differed from the assemblages in presence of tadpoles. A. laureatus presented higher mass in presence of tadpoles; however, tadpole length was not affected by presence of macroinvertebrates. Our results suggest that presence of tadpoles is a driver of periphyton accrual and assemblage structure, acting as top‐down control and with key potential consequences on the functioning of montane stream ecosystems. Abstract : This paper demonstrates that amphibian loss increases periphyton biomass, causes shifts in algal assemblages and reduces invertebrate growth. It highlights the importance of protecting amphibians in order to maintain normal stream ecosystem functioning, especially in nonforested streams where periphyton in the main energy resource. Resumen: La población de anfibios está reduciéndose globalmente debido a una combinación de factores como el cambio climático, las especies invasoras, la pérdida de hábitat, la contaminación y las enfermedades emergentes. Aunque su desaparición probablemente causará consecuencias ecológicas importantes en la estructura y el funcionamiento de los ecosistemas de agua dulce, es un aspecto que ha sido poco explorado. Se realizó un experimento en tres arroyos de montaña, donde la producción primaria es la principal fuente de energía y carbono, para determiner los efectos de la desaparición de los anfibios (presencia o ausencia del sapo partero común Alytes obstetricans, una especie común en pozas de estos arroyos) en varios aspectos del funcionamiento y la estructure del ecosistema: la biomasa de perifiton y la concentración de clorofila, la estructura de la comunidad algal y el crecimiento de los macroinvertebrados raspadores. Comparamos cuatro tipos de recintos: (i) sin macroinvertebrados ni anfibios; (ii) con larvas del tricóptero Allogamus laureatus ; (iii) con renacuajos de A. obstetricans ; y (iv) con tanto larvas de A. laureatus como renacuajos de A. obstetricans . La ausencia de renacuajos aumentaba la biomasa de perifiton, aunque no causaba diferencias en la acumulación de sedimento inorgánico. La comunidad de algas presentaba una mayor diversidad en ausencia de renacuajos, y sus taxones característicos eran distintos de los de las comunidades con presencia de renacuajos. A. laureatus tenía una mayor masa en presencia de renacuajos, pero la longitud de los renacuajos no se veía afectada por la presencia de macroinvertebrados. Nuestros resultados sugieren que la presencia de renacuajos controla la acumulación de perifiton y la estructura de las comunidades, ejerciendo un control de arriba hacia abajo, con consecuencias clave en el funcionamiento de los ecosistemas de arroyos de montaña.